A Safe Space Amid Debt: Social and Cultural Practices in In-donesia's Digital Community of Online Loan Default Survi-vors - Gusti Louisa; Augustin Mustika Chairil (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This article examines how a group of people sharing the experience of online loan default builds its own social and cultural order in digital space, using the Facebook group "Galbay Pinjol 2026" as a case. Employing a netnographic approach, data were gathered from four months of group observation (March–June 2026) and in-depth interviews with seven purposively selected members. The findings show that this space functions as more than a venue for venting; it operates as a social ecosystem sustained by four interlocking dimensions: the emergence of a distinct vocabulary and set of symbols marking group identity; unwritten norms and an "us versus them" construction that binds solidarity; the community’s role as a social safety net that mobilizes collective action; and varied member attitudes toward risky information, ranging from collective vigilance to openings for questionable practices. The article concludes that such communities constitute a complex digital social space in which language, identity, norms, and solidarity are continuously woven together in response to shared financial pressure and stigma.